Surgical outcomes of sacrospinous hysteropexy and hysteropreservation for pelvic organ prolapse: a systematic review of randomized controlled trials - Xiao, Xinyu; Yu, Xia; Yin, Litong; Zhang, Ling; Feng, Dan; Zhang, Lushuang; Gong, Zhaolin; Zhang, Qiang; Lin, Yonghong; He, Li (Frontiers in Medicine, 2024)
Objective In several randomized controlled trials (RCTs), sacrospinous hysteropexy and other forms of hysteropreservation have been compared. Nevertheless, there is no definitively best treatment. This study summarized RCT evidence for various uterine preservation surgical procedures. Methods From each database inception to August 2023, we searched PubMed, Embase, Cochrane Library, and Web of Science for eligible RCTs. A comparison was made between sacrospinous hysteropexy and other hysteropreservation, including vaginal and abdominal surgery. For categorical and continuous variables, relative risks (RRs) and mean differences (MDs) were calculated using random-effects models. Results We reviewed a total 1,398 studies and ultimately included five RCTs that met all inclusion criteria. These five studies included a total of 1,372 uterine POP cases all of whom received transvaginal surgery and had a follow-up period for assessment of recurrence from 12 months to 5 years. There were no significant differences between sacrospinous hysteropexy and other hysteropreservation for the incidences of recurrence (RR,1.24; 95% CI, 0.58 to 2.63; p = 0.58) or hematoma (RR,0.70; 95% CI, 0.17 to 2.92; p = 0.62). Moreover, neither sacrospinous hysteropexy nor hysteropreservation had any significant effect on the risk of mesh exposure (RR,0.34; 95% CI, 0.03 to 4.31; p = 0.41), dyspareunia (RR,0.45; 95% CI, 0.13 to1.6; p = 0.22), urinary tract infection (RR,0.66; 95% CI, 0.38 to 1.15; p = 0.15), bothersome bulge symptoms (RR,0.03; 95% CI, −0.02 to 0.08; p = 0.24), operative time (MD, −4.53; 95% CI, −12.08 to 3.01; p = 0.24), and blood loss (MD, −25.69; 95% CI, −62.28 to 10.91; p = 0.17). However, sacrospinous hysteropexy was associated with a lower probability of pain (RR,4.8; 95% CI, 0.79 to 29.26; p = 0.09) compared with other hysteropreservation. Conclusion There was no difference between sacrospinous hysteropexy and hysteropreservation in terms of recurrence, hematoma, mesh exposure, dyspareunia, urinary tract infection, bothersome bulge symptoms, operative time, pain, and blood loss. Systematic Review Registration PROSPERO [CRD42023470025].